2020
DOI: 10.1007/s10993-020-09543-3
|View full text |Cite
|
Sign up to set email alerts
|

Affects of verbal hygiene: the impact of language activism at a Swedish high school

Abstract: This paper explores youths' language activism at a Swedish senior high school. Following Cameron (Verbal hygiene, Routledge, Florence, 1995), this paper investigates language activism as 'verbal hygiene', with a focus on the social dimension of students' attempts to change how language is used at the school. To capture how the politically motivated language activism came to produce political subjectivities and delineation between social groups, and also to impact the distribution of agency and voice in the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…As observed by Cameron (1995) and Curzan (2014), verbal hygiene appears to be one of the universals of human linguistic practice : as soon as two ways of saying (roughly) the same thing become available to language users, some of those users will start formulating opinions about whether one grammatical variant is better than the other, and encouraging others to use what they consider to be the superior one. Research into verbal hygiene has shown that there exist a large range of normative discourses regulating linguistic practices, and that verbal hygiene practices vary across languages, time periods, and social contexts (Paffey, 2007;Cameron, 2013;Jones, 2013;Årman, 2021;Brown, 2022, among many others).…”
Section: Verbal Hygienementioning
confidence: 99%
“…As observed by Cameron (1995) and Curzan (2014), verbal hygiene appears to be one of the universals of human linguistic practice : as soon as two ways of saying (roughly) the same thing become available to language users, some of those users will start formulating opinions about whether one grammatical variant is better than the other, and encouraging others to use what they consider to be the superior one. Research into verbal hygiene has shown that there exist a large range of normative discourses regulating linguistic practices, and that verbal hygiene practices vary across languages, time periods, and social contexts (Paffey, 2007;Cameron, 2013;Jones, 2013;Årman, 2021;Brown, 2022, among many others).…”
Section: Verbal Hygienementioning
confidence: 99%
“…An analysis of how emotions are semiotically materialized through affective-discursive practice needs to be embedded in a relevant intersubjective setting. Such an intersubjective setting can be achieved using different methodologies, for example, ethnography (Årman, 2020), interactional analysis (Franzèn et al, 2020; Kiesling, 2018) or intertextual analysis (Westberg, 2020), as well as through the interpretative technique I choose to call here strategic perspectivation . This technique is inspired by Janks’ (2010) work on critical literacy.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Within the field of multimodal discourse studies, affect is currently gaining attention as a starting point for investigating how power and social forces are enacted through different modes of communication. In relation to diverse political and social phenomena such as homosocial belonging (Franzèn et al, 2020; Kiesling, 2018), neo-Nazi recruitment (Westberg, 2021), premium tourism and traveling (Björkvall et al, 2020; Thurlow, 2020), queer- and language activism (Årman, 2020; Milani, 2015) and the rise of right-wing populism (Breeze, 2019; Wodak, 2015), scholars point to the importance of acknowledging multimodal communication for its potential to accomplish affective meaning-making (cf. Milani and Køhler Mortensen, 2020; Wetherell, 2012).…”
mentioning
confidence: 99%
“…This brings us to the theoretical challenge of encircling affect not only as a somatic or psychological, but also as a semiotic and discursive phenomenon. Whereas Lefebvre ties the affective dimensions of space to lived space, we draw on Wetherell's (2012Wetherell's ( , 2013Wetherell et al 2015) notion of affect as discursive practice (see also Ahmed 2004;Årman 2020;Franzén, Jonsson, and Sjöblom 2020;Kiesling 2018;Milani 2015;Westberg 2021). From this perspective, affect is not "only" lived, embodied, and experienced, but also semiotically and discursively enacted through spatial resources with affective meaning potential.…”
Section: The Airport As Affective Space and Placementioning
confidence: 99%